Under the steel yoke : poems - Mzinyathi, Jabulani (Mwanaka Media and Publishing (Mmap) Pvt Ltd, 2018)
In Under The Steel Yoke I hear the wailing of fellow citizens as leadership subversion takes root. When servants become masters- that is a subversion, waves of despair threaten our people. I attempt to reflect the resilience of fellow Zimbabweans as we fight on for survival, hope refuses to die. The ideals of the true liberators prick our collective conscience. These poems are meant to provoke debate about nation building and they are an assertion that there can never be peace without justice. These poems are the voices heard on the streets, in pubs, factories, churches, homes and wherever our people irk a living. These voices yearn for a glorious future.